Criteria for establishing the diagnosis of multifocal motor neuropathy without conduction blocks: a case study - Mishura, Svitlana; Prokopiv, Maria; Illiash, Tetiana (The Ukrainian Scientific Medical Youth Journal, 2025)
the article is devoted to the determination of clinical features of multifocal motor neuropathy without conduction blocks based on the literature, clinical and electrophysiological results of the patient's examination. The article presents current data on the prevalence, difficulties in timely diagnosis and main clinical features of multifocal motor neuropathy. A clinical case is presented. Patient Z., 55 years old, complained of weakness in the limbs, painful muscle cramps and gait disturbance. She has been ill since 2010, when she began to feel weakness in her right hand with difficulty in its extension. A few months later, weakness in the left leg appeared. In 2014, the weakness of the right hand became significant, and in 2018, the weakness of the right leg was added. The patient was previously diagnosed with spinal amyotrophy. The family history is unencumbered. Neurological status: significant peripheral, more distal tetraparesis, especially on the right, no flexion of both hands and right foot, significant muscle atrophy in the distal extremities, more in the arms, especially the right. Muscle tone of the upper extremities is low, lower extremities - with a tendency to decrease, deep reflexes of the arms, legs and plantar reflexes are absent, no sensory disorders. Electrophysiological signs of a chronic neurogenic process, conduction blocks were not detected. A differential diagnosis was made with amyotrophic lateral sclerosis, spinal muscular atrophy, chronic inflammatory demyelinating polyradiculoneuropathy. The patient had the following main clinical signs: slow gradual onset of the disease, disorders in several motor nerves that occurred alternately in several months, asymmetry of manifestations. Auxiliary electrophysiological criteria were also established - signs of axonal lesions of motor and partially sensitive fibers of all peripheral nerves without conduction blocks. These clinical and auxiliary electrophysiological parameters confirm the literature data on the clinical features of MMN and indicate the presence of multifocal motor neuropathy without conduction blocks.